2018
DOI: 10.26701/ems.369005
|View full text |Cite
|
Sign up to set email alerts
|

Bio-composite materials: a short review of recent trends, mechanical and chemical properties, and applications

Abstract: Recently, the attraction on the bio-composite (known as green composites) materials has significantly increased due to the potential of being substitute to conventional materials used in manufacturing industries. Biocomposite materials are produced with natural fibers or natural resins instead of synthesized fibres (carbon, glass, etc fibers) or resins (poly vinyl alcohol, epoxy, etc resins). The bio-based fibers such as jute, sisal, flax, hemp, bamboo, hair, wool, silk etc., are obtained from plants or animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 108 publications
0
26
0
Order By: Relevance
“…Broad application of biocomposites in polymer materials processing and production was noticed over the last decades [ 1 , 2 , 3 , 4 ]. This trend occurs due to the multiple benefits related to the biocomposites production methods as well as their exploitation potential and ease of disposal [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Broad application of biocomposites in polymer materials processing and production was noticed over the last decades [ 1 , 2 , 3 , 4 ]. This trend occurs due to the multiple benefits related to the biocomposites production methods as well as their exploitation potential and ease of disposal [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fiber selection with the inclusion of product time, along technique, appearance proportion, handling and fiber ingredient, matrix choice, interfacial resistance, fiber distribution, fiber orientation, composite producing method and porosity are the main factors impressing the properties of PFRCs. Some mechanical properties of PFRCs was shown in Table 4 [15]. Jute fiber as strengthen material for PP composites were utilized by Rahman et al Jute fiber was processed with maleic acid and the results were observed.…”
Section: Properties Of Prfcsmentioning
confidence: 99%
“…[ 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 ]. The most commonly used materials for biocomposites are thermoplastics and thermoset resins including polypropylene (PP), polystyrene (PS), polyethylene (PE), polyvinylchloride (PVC), epoxy resin, vinyl esters, polyesters and phenol-formaldehyde [ 20 ]. Moreover, attempts have been made to create synthetic rubber-thermoplastic blends reinforced with natural filler [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%